2009
DOI: 10.1186/2047-783x-14-6-256
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcome after posterior versus lateral surgical approach for total hip arthroplasty - a randomized clinical trial*

Abstract: PurposeCurrently, total hip replacement (THR) is most commonly performed via a posterior or a direct lateral approach, but the impact of the latter on the invention's outcome has yet not been quantified.MethodsWe compared the short-term outcome of cementless THR using the both approaches in a prospective, randomized controlled trial. 60 patients with unilateral osteoarthritis were included. Outcome assessment was performed one day before surgery and one week, four weeks, six weeks and 12 weeks after surgery, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…The rate of dislocation and fracture did not differ significantly between the groups. [25][26][27] Harris hip score in our study also favors that there is no significant difference with either approach. A common comparator between the posterior and lateral approach is the incidence of abductor insufficiency.…”
Section: Discussionsupporting
confidence: 66%
“…The rate of dislocation and fracture did not differ significantly between the groups. [25][26][27] Harris hip score in our study also favors that there is no significant difference with either approach. A common comparator between the posterior and lateral approach is the incidence of abductor insufficiency.…”
Section: Discussionsupporting
confidence: 66%
“…Historically, the posterior and direct lateral approaches have been the most commonly used techniques, both with advantages and disadvantages [1][2][3]. The direct lateral approach has often been associated with persistent postoperative abductor dysfunction and limp.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested the direct lateral approach has an increased incidence of abductor insufficiency following THA. 15,24,30,56 The reported incidence varies from 0% to 16% for the posterior approach and from 4% to 20% for the direct lateral approach. 15 However, there is tremendous heterogeneity in the methods used to diagnose abductor insufficiency in many of these studies.…”
Section: Lateral Versus Posterior Approachmentioning
confidence: 99%
“…A more recent prospective study 56 randomly assigned 60 patients to undergo THA through either a posterior or lateral approach. The primary end point was the HHS at the 12-week follow-up.…”
Section: Lateral Versus Posterior Approachmentioning
confidence: 99%